Oreocharis hapii (Gesneriaceae), a new species from central Vietnam - Nguyen, Khang Sinh; Averyanov, Leonid V.; Lin, Che Wei (Phytotaxa, 2024)
Oreocharis hapii, a new species endemic to Quang Nam Province in central Vietnam, is described and illustrated here. This species bears a superficial resemblance to O. cotinifolia in its elliptic leaves, campanulate corolla tube, and the stamens protruding from the tube. However, the new species differs in its stoloniferous habit (vs. absent stolons), petioles and stems densely woolly (vs. villous), leaf blade adaxially scabrous (vs. villous), sub-actinomorphic corolla (vs. distinctly zygomorphic) that is white (vs. pink) with 4 stamens (vs. 2). Following IUCN criteria, the conservation status of the new speciesis proposed to be Vulnerable (VU: D1).